The Cigar Tobacco Industry in East Java: Facing an Uncertain Future? - McMichael, Heath (OECONOMICUS Journal of Economics, 2024)
Tobacco has historically been a significant cash crop in Indonesia, with the tobacco manufacturing industry contributing about 0. 69 percent to the country's GDP in 2022, generating revenue of around USD 35 billion. The tobacco industry plays a crucial role in employment, economic growth, and tax revenue collection, particularly in regions like East Java, focusing on high-quality tobacco and cigar production. The paper delves into tobacco cultivation in East Java, specifically Jember, and examines trading relationships, price arrangements, and the economic and health implications of cigar tobacco. It highlights the history of tobacco in Indonesia, including the transition from Dutch-owned plantations to small-scale tobacco production for cigarettes. The fluctuating supply and demand of tobacco in Indonesia have been influenced by global factors, with implications for local farmers and the export market, particularly to the Dominican Republic and China